Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài làm:
Ta có: \(3x^2+3x-6\)
\(=\left(3x^2+6x\right)-\left(3x+6\right)\)
\(=3x\left(x+2\right)-3\left(x+2\right)\)
\(=3\left(x-1\right)\left(x+2\right)\)
\(3x^2+3x-6\)
\(=3\left(x^2+x-2\right)\)
\(=3\left(x^2+2x-x-2\right)\)
\(=3\left[x\left(x+2\right)-\left(x+2\right)\right]\)
\(=3\left(x-1\right)\left(x+2\right)\)
a. = \(6x^2+3x+12x+6=3x\left(2x+1\right)+6\left(2x+1\right)=\left(2x+1\right)\left(3x+6\right)=3\left(2x+1\right)\left(x+2\right)\)
b. \(=6x^2-3x-12x+6=3x\left(2x-1\right)-6\left(2x-1\right)=3\left(2x-1\right)\left(x-2\right)\)
c. \(=6x^2+2x+18x+6=2x\left(3x+1\right)+6\left(3x+1\right)=\left(2x+6\right)\left(3x+1\right)=2\left(x+3\right)\left(3x+1\right)\)
d. \(=6x^2-2x-18x+6=2x\left(3x-1\right)-6\left(3x-1\right)=2\left(x-3\right)\left(3x-1\right)\)
(+) 6x^2 + 15x + 6 = 6x^2 + 12x + 3x + 6
= 6x ( x+ 2 ) + 3 ( x + 2)
= ( 6x + 3) ( x + 2 )
= 3 (2 x + 1 ) ( x + 2)
(+) 6x^2 - 15x + 6 = 6x^2 - 3x - 12x + 6
= 3x( 2x - 1 ) - 6 ( 2x - 1 )
= ( 3 x - 6 )( 2x - 1)
= 3 ( x- 2 ) (2x- 1)
a. \(=6x^2-4x-9x+6=2x\left(3x-2\right)-3\left(3x-2\right)=\left(3x-2\right)\left(2x-3\right)\)
b. \(=6x^2+4x+9x+6=2x\left(3x+2\right)+3\left(3x+2\right)=\left(3x+2\right)\left(2x+3\right)\)
Ta có: \(-8x^2+23x+3\)
\(=\left(-8x^2+24x\right)-\left(x-3\right)\)
\(=-8x\left(x-3\right)-\left(x-3\right)\)
\(=\left(-8x-1\right)\left(x-3\right)\)
\(=\left(3-x\right)\left(8x+1\right)\)
\(-8x^2+23x+3\)
\(=-\left(8x^2-23x-3\right)\)
\(=-\left(8x^2-24x+x-3\right)\)
\(=-\left[8x\left(x-3\right)+\left(x-3\right)\right]\)
\(=-\left(8x+1\right)\left(x-3\right)\)
a) x2 – 3x + 2 = a) x2 – x - 2x + 2 = x(x - 1) - 2(x - 1) = (x - 1)(x - 2)
Hoặc x2 – 3x + 2 = x2 – 3x - 4 + 6
= x2 - 4 - 3x + 6
= (x - 2)(x + 2) - 3(x -2)
= (x - 2)(x + 2 - 3) = (x - 2)(x - 1)
b) x2 + x – 6 = x2 + 3x - 2x – 6
= x(x + 3) - 2(x + 3)
= (x + 3)(x - 2).
Bài giải:
a) x2 – 3x + 2 = a) x2 – x - 2x + 2 = x(x - 1) - 2(x - 1) = (x - 1)(x - 2)
Hoặc x2 – 3x + 2 = x2 – 3x - 4 + 6
= x2 - 4 - 3x + 6
= (x - 2)(x + 2) - 3(x -2)
= (x - 2)(x + 2 - 3) = (x - 2)(x - 1)
b) x2 + x – 6 = x2 + 3x - 2x – 6
= x(x + 3) - 2(x + 3)
= (x + 3)(x - 2).
c) x2 + 5x + 6 = x2 + 2x + 3x + 6
= x(x + 2) + 3(x + 2)
= (x + 2)(x + 3)
\(x^3+3x^2-4\)
\(=\left(x^3+4x^2\right)-\left(x^2+4\right)\)
\(=\left(x^2+4\right)\left(x-1\right)\)
Mình nhìn nhầm đề
\(x^3+3x^2-4\)
\(=\left(x^3+2x^2\right)+\left(x^2-4\right)\)
\(=x^2\left(x+2\right)+\left(x-2\right)\left(x+2\right)\)
\(=\left(x+2\right)\left(x^2+x-2\right)\)
\(=\left(x+2\right)\left[\left(x^2+x\right)-\left(2x+2\right)\right]\)
\(=\left(x+2\right)\left(x+2\right)\left(x-1\right)\)
\(=\left(x+2\right)^2\left(x-1\right)\)
\(1,3x^2+3x-6=3x^2-3x+6x-6=\left(3x^2-3x\right)+\left(6x-6\right)=3x\left(x-1\right)+6\left(x-1\right)=\left(x-1\right)\left(3x+6\right)\)
\(2,6x^2-13x+6=6x^2-4x-9x+6=\left(6x^2-4x\right)-\left(9x-6\right)=2x\left(3x-2\right)-3\left(3x-2\right)=\left(3x-2\right)\left(2x-3\right)\)